Study of production technology for pennywort powder product by cold-drying method - Dang, Thi Cuong; Pham, Thanh Tung; Do, Thuy Khanh Linh; Nguyen , Dang My Duyen; Nguyen , Tan Dzung (Journal of Technical Education Science, 2020)
The aim of this research was to develop and solve the experimental mathematical model which described the cold-drying process to produce pennywort powder products. Results obtained were to build the multi-objective optimization for cold-drying process of pennywort and the product after drying was good quality, the moisture content met the requirements and the energy cost reached the lowest level. The technological mode of cold-drying process for pennywort was found out by solving multi-objective optimization as follows: the optimal drying temperature was 44.24oC, the optimal drying time was 14.12 hours and the optimal drying velocity was 12.83 m/s. Corresponding to these optimal factors, the solute concentration reached the minimum value of 11.31%; moisture content reached the minimum value of 3.65%; ΔE of 2.056 while the energy consumption for 1 kg final product reached the minimum value of 1.1 kWh / kg.